2007
DOI: 10.1002/micr.20367
|View full text |Cite
|
Sign up to set email alerts
|

Review of vascularized bone marrow transplantation: Current status and future clinical applications

Abstract: In this review, we examine the applicability of the vascularized bone marrow transplant (VBMT) as an alternative to conventional bone marrow transplantation (BMT). As a new surgical approach, the VBMT is unique by transplantation of the stromal environment that eliminates the need for an engraftment period, provides critical signaling and modulatory functions, and may potentiate tolerance induction. Thus far, VBMT studies have demonstrated an absence of graft-versus-host disease (GVHD) and robust engraftment i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…These studies confirmed the superiority of VBMT for the hematopoietic reconstitution of donor bone marrow cells when compared with cellular bone marrow transplantations (BMT). [3][4][5][6][15][16][17][18][19][20][21][22][23] In their recent comprehensive review on VBMT, Gordon et al examined the newly found benefits, the unique characteristics and the applicability of VBMT as an alternative to BMT. They emphasized the importance of VBMT to potentially reduce the risk of engraftment failure, provide a more rapid engraftment, enhance cellular function, reduce graft-versus-host disease, and aid in inducing immunologic tolerance.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These studies confirmed the superiority of VBMT for the hematopoietic reconstitution of donor bone marrow cells when compared with cellular bone marrow transplantations (BMT). [3][4][5][6][15][16][17][18][19][20][21][22][23] In their recent comprehensive review on VBMT, Gordon et al examined the newly found benefits, the unique characteristics and the applicability of VBMT as an alternative to BMT. They emphasized the importance of VBMT to potentially reduce the risk of engraftment failure, provide a more rapid engraftment, enhance cellular function, reduce graft-versus-host disease, and aid in inducing immunologic tolerance.…”
mentioning
confidence: 99%
“…They emphasized the importance of VBMT to potentially reduce the risk of engraftment failure, provide a more rapid engraftment, enhance cellular function, reduce graft-versus-host disease, and aid in inducing immunologic tolerance. 16 Different VBMT models were introduced in the literature, including marrow sources from the limb, sternum, femoral bone, and bilateral vascularized femoral bones. 3-6,16 -23 In addition, we have introduced different models of face allotransplantation in rats including a full-face, hemi-face and hemiface/calvaria model.…”
mentioning
confidence: 99%
“…This phenomenon has been demonstrated in several VBM transplant models in rats using limb, sternum, bone in vascularized continuity with the composite transplant, and alternate-recipient site femoral bone transplants. 17,[27][28][29] Additionally, graft-versus-host-disease (GVHD) has not developed following VBM transplantation, supporting the use of VBM contained in composite grafts as an immunomodulatory strategy. 9 The rat combined SIEA myocutaneous/vascularized femur transplant is a promising single-anastomosis model to explore the contributions of VBM to VCA survival, as the VBM component can be either included or excluded without major technical modifications.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18] For instance, abdominal wall transplants contain large skin/muscle components and accompany no underlying bone. In contrast, CTAs containing bone, such as osteocutaneous face and hand, may contain a tolerogenic advantage analogous to vascularized bone marrow transplantation, 19,20 which is present in osteocutaneous face and hand transplants.…”
Section: Immunologic Problemsmentioning
confidence: 97%